IMPLEMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER PADA SISWA: SD NEGERI JERUK SOKSOK 1 - JAROT JAROT (Mitra Pendidikan, 2022)
Numbered Heads Together is a learning method with a numbering system that prioritizes interaction patterns between students who are formed in groups of students and always work cooperatively in answering questions given by the teacher. understanding NHT is a type of structural approach cooperative learning that provides opportunities for students to share ideas and consider the most appropriate answers. In addition, Numbered Heads Together also encourages students to increase their cooperation. This model can be used for all subjects and all levels of learners. This research is entitled "Implementation of the Numbered Heads Together Learning Model in Class VI Students of SDN Jeruk Soksok 1 Even Semester for the 2021/2022 Academic Year". This research is classroom action research and is included in the scope of applied research which combines knowledge, research, and action. This research was held for 2 months, from October to November 2022. The results of this research show that the Numbered Head Together model of cooperative learning has a positive impact on improving student achievement and learning outcomes as well as mastery of the subject matter that has been received so far, which can be shown by the increase in the average value of students in each activity that continues to increase.